How Do Innovation, Quality, And Supply Chain Management Affect Customer Satisfaction in Organic Food Products?: Evidence From Jabodetabek, Indonesia - Mustafa, Fahrina; Hendra, Hendra; Ibrahim, Mozart Malik; Astuti, Desi; Pandiangan, Bilson (Universitas Negeri Gorontalo, 2024)
This study investigates the influence of product innovation, supply chain management, and product quality on customer satisfaction in the organic food sector. A quantitative approach was employed using survey data collected from 120 organic food consumers in the Jabodetabek area. The data were analyzed using multiple linear regression analysis to determine the impact of each variable. The findings indicate that all three factors product innovation, supply chain management, and product quality have a significant and positive influence on customer satisfaction. Notably, innovations in eco-friendly packaging, product variety, and transparency in supply chain operations contribute significantly to enhancing customer perceptions and trust. These results underscore the critical role of integrated management practices and continuous product development in sustaining customer loyalty and satisfaction in the growing organic food market.